Frequency and characteristics of impaired fasting glucose in trujillo adults according diagnostic criteria - Castillo Minaya, Karen Yanet (2011)
Objetive: Impaired fasting glucose (IFG) is a reversible transitory state to diabetes mellitus. To compare IFG frequency according to the American Diabetes Association (ADA) and the World Medical Association (WMA) criteria, and its characteristics in adults from Trujillo according age and gender. Material and methods: 224 male and 232 women from Trujillo, in age groups from 20 to 39, 40 to 59 and 60 to 79 years old. Clinic and biochemical assays (glucose and profile lipid blood) were done, considering IFG according ADA: 100 a 125 mg/dl and OMS: 111 a 125 mg/dl Results: IFG prevalence according ADA, adjusted by age: male 11,73; women 13,61 and total 12,64%; withouth difference by gender and increased with age. IFG prevalence according OMS, adjusted by age: male 4,55; women 2,46 and total 3,49% and increased with age .IFG according ADA had as risk factors with significative OR: obesity (2,14), increased BMI (2,42), arterial hypertension (2,19), increased blood pressure according metabolic syndrome (IBPAMS) (3,06), HDL according SM (1,94) and as an ATPIII criteria (2,07) with frequencies of 18,57%; 71,43%; 37,14%; 52,86%; 51,43% and 27,14% respectively. In IFG according OMS: arterial hypertension (6,45), IBPAMS (4,07), HDL <40 mg/dl (2,95) and hypercholesterolemia (4,51) with frequencies of 72,73%; 54,55%; 36,36% and 59,09% respectively. Conclusions: In Trujillo, the frequency of IFG according ADA almost quadruplicates IFG according OMS and increase with age, without gender difference.